SNX10 Is Involved in Ovarian Cancer Cell Metastasis by Repolarizing Tumor-Associated Macrophages Through mTOR1/Lysosomes Pathway - Ranran Chai; Kewei Zheng; Ting Xu; Hui Wang; Xiaobo Cheng; Chong Lu; Yu Kang (Biomedicines)
Background: Tumor-associated macrophages (TAMs) are prevalent in advanced ovarian cancer tissues and ascites, significantly influencing disease prognosis. However, the mechanisms driving TAM polarization and their tumor-promoting effects remain poorly understood. Methods: The subcellular distribution of SNX10 in ovarian cancer tissues was analyzed using single-cell datasets (GSE147082, GSE58937). The Kaplan–Meier Plotter and GEPIA2 databases were used to evaluate SNX10’s prognostic relevance. Lentivirus-mediated SNX10 overexpression in THP-1 cells was employed in tumor cell–macrophage co-culture experiments. Transwell assays and flow cytometry assessed SNX10’s effects on ovarian cancer cell metastasis and cisplatin-induced apoptosis. RNA sequencing, Western blotting, lysosomal pH detection, lipid droplet staining, and RT-qPCR were performed to explore SNX10’s molecular mechanisms in TAM polarization and immune modulation. Results: SNX10 was specifically expressed in TAMs, promoting their polarization into the M2 phenotype. This enhanced the migration and invasion of ovarian cancer cell lines A2780 and A2780/CP70 while reducing cisplatin-induced apoptosis. SNX10 decreased lipid droplet content, downregulated p-mTOR1, and impaired lysosomal function in TAMs. Additionally, SNX10 differentially modulated PD-L1 mRNA expression in platinum-sensitive and platinum-resistant ovarian cancer cells. Conclusions: SNX10 regulates the mTOR1/lysosome pathway in TAMs, influencing lipid metabolism and indirectly modulating ovarian cancer cell metastasis. It also alters PD-L1 mRNA expression, suggesting a role in shaping the tumor immune microenvironment.